2023
DOI: 10.1109/tcyb.2022.3194149
|View full text |Cite
|
Sign up to set email alerts
|

Regionwise Generative Adversarial Image Inpainting for Large Missing Areas

Abstract: Recently deep neural networks have achieved promising performance for in-filling large missing regions in image inpainting tasks. They have usually adopted the standard convolutional architecture over the corrupted image, leading to meaningless contents, such as color discrepancy, blur and other artifacts. Moreover, most inpainting approaches cannot handle well the case of a large contiguous missing area. To address these problems, we propose a generic inpainting framework capable of handling incomplete images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Images of persons seated behind the table were included in our proprietary dataset. LaMa [105], MADF [48], Regionwise [113], and AOTGAN [114] were chosen for comparison since they were based on a large mask inpainting method, suitable for human-like forms and thus were similar in this regard to our approach. We have also included a state of the art method E2FGVI [115], operating on semantic masks, as it claims the best accuracy of most recent methods.…”
Section: B Experimental Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Images of persons seated behind the table were included in our proprietary dataset. LaMa [105], MADF [48], Regionwise [113], and AOTGAN [114] were chosen for comparison since they were based on a large mask inpainting method, suitable for human-like forms and thus were similar in this regard to our approach. We have also included a state of the art method E2FGVI [115], operating on semantic masks, as it claims the best accuracy of most recent methods.…”
Section: B Experimental Settingsmentioning
confidence: 99%
“…where Q ⊂ R n and F is a vector of the objective functions CP U 4208 1.03 MADF [48] GP U 405 4.03 RegionWise [113] CP U 4586 0.66 RegionWise [113] GP U 312 3.66 AOTGAN [114] CP U 6248 1.25 AOTGAN [114] GP U 784 4.84…”
Section: E Performance Evaluationmentioning
confidence: 99%
“…Phutke et al [29] suggested computationally efficient, lightweight networks for image restoration with minimal parameters and without guidance information. Ma et al [30] presented a versatile restoration framework capable of addressing incomplete images exhibiting considerable missing regions, encompassing both continuous and discontinuous areas. Region operations are implemented in the generator and discriminator, catering to distinct region types specifically, existing and missing regions.…”
Section: Advanced Deep Learning Approaches For Image Restoration and ...mentioning
confidence: 99%
“…With the advancement of deep learning, object classification and detection techniques have found application in various domains [28,29]. Existing object detection approaches in campus scenarios often involve the direct application of traditional closed-set detection models to the classroom environment.…”
Section: Object Detection In Campus Scenariosmentioning
confidence: 99%